2016
DOI: 10.1097/moo.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Review of adult laryngotracheal stenosis: pathogenesis, management, and outcomes

Abstract: While adult LTS is a complex, challenging clinical entity, there is promising research into the inflammatory origins of the disorder, which may open up groundbreaking new avenues of medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…2 The diagnosis and management of tracheal stenosis pose a conundrum for clinicians as it may masquerade as a spectrum of respiratory ailments from mild wheeze to frank stridor and exertional dyspnea. 5 Patients generally present with decreased exercise tolerance due to dyspnea with stridor elicited only on exertion. Patients with a preexisting cough may report an increase in the amount of sputum with difficulty in coughing it out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The diagnosis and management of tracheal stenosis pose a conundrum for clinicians as it may masquerade as a spectrum of respiratory ailments from mild wheeze to frank stridor and exertional dyspnea. 5 Patients generally present with decreased exercise tolerance due to dyspnea with stridor elicited only on exertion. Patients with a preexisting cough may report an increase in the amount of sputum with difficulty in coughing it out.…”
Section: Discussionmentioning
confidence: 99%
“…2 While a plethora of data is available regarding the predictors of surgical success, improvisation of surgical techniques, anticipated complications and success rates, very few studies are available which view the determining factors and outcomes from the patients' perspective. [3][4][5][6][7][8] Though widely considered a safe procedure with minimal mortality and morbidity, it remains an intricate, invasive procedure which has a major impact on the patients' quality of life (QoL). The incidence of risks is minimal if literature is to be believed, but the risks have far-reaching consequences as far as the individual patient is concerned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other types of lasers are also used, such as KTP laser and Nd:YAG laser. Electrocautery, radiofrequency, and coblation with mechanical dilation using bougies, tracheal tubes, or an expansion balloon catheter are also a consideration [18][19][20] . Monnier et al suggested that endoscopic CO2 laser resection with or without dilation be used in grade I, some grade II, and mild grade III SGS with lengths less than 1.5 cm, and open surgery should be considered for grades II, III, and IV SGS or stenosis greater than 1.5 cm 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Other types of lasers are also used, such as KTP laser and Nd:YAG laser. Electrocautery, radiofrequency, and coblation with mechanical dilation using bougies, tracheal tubes, or an expansion balloon catheter are also a consideration ( 18 - 20 ). Monnier et al .…”
Section: Discussionmentioning
confidence: 99%